Radiation and Dose-densification of R-CHOP in Primary Mediastinal B-cell Lymphoma: Subgroup Analysis of the UNFOLDER Trial - Gerhard Held; Lorenz Thurner; Viola Poeschel; German Ott; Christian Schmidt; Konstantinos Christofyllakis; Andreas Viardot; Peter Borchmann; Walburga Engel-Riedel; Norbert Frickhofen; Maike Nickelsen; Ofer Shpilberg; et al. (HemaSphere, 2023)
UNFOLDER (NCT00278408, EUDRACT 2005-005218-19) is a phase-3 trial in patients with aggressive B-cell lymphoma and intermediate prognosis, including primary mediastinal B-cell lymphoma (PMBCL). In a 2 × 2 factorial design, patients were randomized to 6× R-CHOP-14 or R-CHOP-21 (rituximab, cyclophosphamide, doxorubicin, vincristine, and prediso(lo)ne) and to consolidation radiotherapy to extralymphatic/bulky disease or observation. Response was assessed according to the standardized criteria from 1999, which did not include F-18 fluordesoxyglucose positron emission tomography/computed tomography (FDG-PET) scans. Primary end point was event-free survival (EFS). A subgroup of 131 patients with PMBCLs was included (median age, 34 y; 54% female, 79% elevated lactate dehydrogenase (LDH), 20% LDH >2× upper limit of normal [ULN], and 24% extralymphatic involvement). Eighty-two (R-CHOP-21: 43 and R-CHOP-14: 39) patients were assigned to radiotherapy and 49 (R-CHOP-21: 27, R-CHOP-14: 22) to observation. The 3-year EFS was superior in radiotherapy arm (94% [95% confidence interval (CI), 89-99] versus 78% [95% CI, 66-89]; P = 0.0069), due to a lower rate of partial responses (PRs) (2% versus 10%). PR triggered additional treatment, mostly radiotherapy (n = 5; PR: 4; complete response/unconfirmed complete response: 1). No significant differences were observed in progression-free survival (PFS) (95% [95% CI, 90-100] versus 90% [95% CI, 81-98]; P = 0.25) nor in overall survival (OS) (98% [95% CI, 94-100] versus 96% [95% CI, 90-100]; P = 0.64). Comparing R-CHOP-14 and R-CHOP-21, EFS, PFS, and OS were not different. A prognostic marker for adverse outcome was elevated LDH >2× ULN (EFS: P = 0.016; PFS: P = 0.0049; OS: P = 0.0014). With the limitation of a pre-PET-era trial, the results suggest a benefit of radiotherapy only for patients responding to R-CHOP with PR. PMBCL treated with R-CHOP have a favorable prognosis with a 3-year OS of 97%.